Effectiveness of Organic Fertilizer Application in Increasing Organic Coffee (Coffea sp) Productivity and Coffee Bean Fermentation Results in Pentingsari Village: Efektivitas Aplikasi Pupuk Organik dalam Peningkatan Produktivitas Kopi (Coffea sp) Organik dan Hasil Fermentasi Biji Kopi di Desa Pentingsari - Purboseno, Sentot; Hermantoro, Hermantoro; Kadarwati, Kadarwati; Suprianto, Gani (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
This Community Service Program (PKM) aims to increase the productivity of organic robusta coffee and the quality of fermented coffee beans through the application of organic fertilizers and sustainable cultivation practices in Pentingsari Village, Cangkringan District, Sleman Regency, Special Region of Yogyakarta. Pentingsari Village is located on the slopes of Mount Merapi with fertile volcanic soil, making it a potential location for the development of organic coffee farming. Challenges faced by farmers include the use of inorganic fertilizers that damage soil quality and lack of knowledge about organic farming practices. Through a series of counseling, training, and field practice, this program provides education and skills to farmers to adopt better organic farming practices. The results of the activities show an increase in farmers' knowledge about organic coffee cultivation techniques, improvements in coffee bean fermentation methods, and increased productivity and quality of robusta coffee. The implementation of organic fertilizers in agricultural land management has a positive impact on soil fertility and the sustainability of coffee production